2012
DOI: 10.1088/1748-0221/7/01/p01015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a commercial 65 nm CMOS technology for SLHC applications

Abstract: The radiation characteristics with respect to Total Ionizing Dose (TID) and Single-Event Upsets (SEUs) of a 65 nm CMOS technology have been investigated. Single transistor structures of a variety of dimensions and several basic circuits were designed and fabricated. The circuits include a 64-kbit shift-register, a 56-kbit SRAM and a ring-oscillator. The test chips were irradiated up to 200 Mrad with an X-ray beam and the corresponding transistor threshold shifts and leakage currents were measured. Heavy-ion be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 6 publications
4
32
0
Order By: Relevance
“…It offers about four times higher logic density compared to the 130 nm node and has recently been radiation qualified by CERN [82]. It is found not to require special layout of transistors in digital functions to tolerate the HL-LHC radiation environment.…”
Section: A41 Readout Chip Technologymentioning
confidence: 99%
“…It offers about four times higher logic density compared to the 130 nm node and has recently been radiation qualified by CERN [82]. It is found not to require special layout of transistors in digital functions to tolerate the HL-LHC radiation environment.…”
Section: A41 Readout Chip Technologymentioning
confidence: 99%
“…This was confirmed for MOS transistors when they became available with these thin oxides more than a decade later [8]. Now it is common knowledge that transistors of commercial deep submicron CMOS technologies withstand very significant total For instance, in [9] the PMOS of minimum size shows significant current drive degradation which cannot be attributed to its radiation induced threshold voltage shift alone.…”
Section: Charge Collection Mechanism By Drift and Deep Submicron Cmosmentioning
confidence: 84%
“…This curve is compared in figure 6 with the cross section (evaluated in a previous study [6]) of a standard library flip-flop in the same …”
Section: B Seu Sensitivity Resultsmentioning
confidence: 99%
“…Previous studies [6] suggested this value as the minimum needed to assure acceptable performances degradation due to TID in the used 65-nm technology. A more detailed description of the test chip and its components can be found in [8].…”
Section: The Serializersmentioning
confidence: 99%
See 1 more Smart Citation